A responsabilidade civil objetiva como dever fundamental e sua incidência nas relações privadas - SILVA, Adelvan Oliverio (Universidade Federal do Pará, 2015)
The work examines sociological and philosophical foundations of objective liability, specifically the responsibility by the "risk". it assumes that the way most of the civilian doctrine analyzes the institution mitigates the potential for strict liability to be understood as an element of organization of functionally differentiated, characterized by excessive complexity and the radical contingency that permeate the communication made between social systems, among humans and between these and those. it concludes that the risk is an unsurpassed feature of complex societies, and analyzing the consequences of that for the formation of the human been who can commit to a political life, it proposes, based mainly on the philosophical studies of Paul Ricoeur and dogmatic constitutional robert alexy, that liability is objectively high level legal and moral duty of the fundamental subjects of law, primarily in the bulge between the relations among individuals.